Evaluation of new generation macrolides for the treatment and metaphylaxis of contagious bovine pleuropneumonia (CBPP) in cattle experimentally infected with Mycoplasma mycoides subspecies mycoides - Muuka, G.; Otina, B.; Wesonga, H.; Bowa, B.; Gicheru, N.; Poole, Elizabeth J.; Salt, Jeremy; Colston, A. (Springer, 2019)
Contagious bovine pleuropneumonia (CBPP) caused by Mycoplasma mycoides subspecies mycoides (Mmm) is an important disease of cattle that causes serious economic losses. With the known effectiveness of new generation macrolides, tulathromycin and gamithromycin were assessed in comparison with oxytetracycline as a positive control and saline as a negative control for effectiveness in inhibiting lung lesion development, promoting resolution, preventing spread and bacteriological clearance in susceptible local cattle breeds in two separate studies in Kenya and Zambia. Animals were monitored for clinical signs, sero-conversion as well as detailed post-mortem examination for CBPP lesions.Using the Hudson and Turner score for lesion type and size, tulathromycin protected 90%, gamithromycin 80%, and oxytetracycline 88% of treated animals in Kenya. In Zambia, all animals (100%) treated with macrolides were free of lung lesions, while oxytetracycline protected 77.5%. Using the mean adapted Hudson and Turner score, which includes clinical signs, post-mortem findings and serology, tulathromycin protected 82%, gamithromycin 56% and oxytetracycline 80% of the animals in Kenya whereas in Zambia, tulathromycin protected 98%, gamithromycin 94% and oxytetracycline 80%. The saline-treated groups had 93 and 92% lesions in Kenya and Zambia respectively, with Mmm recovered from 5/14 in Kenya and 10/13 animals in Zambia. Whereas the groups treated with macrolides were free from lesions in Zambia, in Kenya 5/15 tulathromycin-treated animals and 6/15 gamithromycin-treated animals showed lesions. Oxytetracycline-treated animals showed similarities with 3/14 and 4/15 showing lesions in Zambia and Kenya respectively and Mmm recovery from one animal in Kenya and six in Zambia. In both studies, lesion scores of saline-treated groups were significantly higher than those of the antibiotic treated groups (p < 0.001). In sentinel animals, CBPP lesions were detected and Mmm recovered from one and two animals mixed with the saline-treated groups in Kenya and Zambia respectively.This study demonstrated that tulathromycin, a mycoplasmacidal, can achieve metaphylactic protection of up to 80%, while non-recovery of Mmm from sentinels suggests macrolides effectiveness in preventing spread of Mmm. It is recommended that further studies are conducted to evaluate strategies comparing vaccination alone or combining vaccination and antibiotics to control or eradicate CBPP.